Terapi Probiotik pada Akne Vulgaris - Reti Anggraeni; Arie Kusumawardani (MEDICINUS, 2021)
Acne vulgaris (AV) is a skin chronic inflammatory disease that affects pilosebaceous unit and results in non-inflammatory abnormalities in the form of open comedones (blackhead) and closed comedones (whitehead) and also inflammatory lesions such as papules, pustules and nodules. Many factors contribute to the pathogenesis of AV including skin microbiomes like Propionibacterium acnes (P. acnes) and Malassezia spp. which is associated through its effect on sebum secretion, comedones formation and inflammatory response. Antibiotic therapy with the target of P. acnes has long been the mainstay of AV therapy where it can actually affect the composition of skin microbiomes. As antibiotic resistance increases, knowledge of skin microbiomes associated with AV becomes very relevant and important to be an alternative basis for AV alternative therapy.